2019
DOI: 10.1080/23311886.2019.1586080
|View full text |Cite
|
Sign up to set email alerts
|

Gender and poverty in South African rural areas

Abstract: In this article, we elicit the effects of gender on poverty reduction efforts in South Africa. Gender plays a huge role in the household decision-making process, as a result, it can determine if whether the household falls into a poverty trap or falls out of poverty. Utilizing a recently Community Survey (2016) we employ a Categorical Principal Component Analysis (CATPCA) to identify potential poverty indicators in South Africa. We then regress the identified components (indicators) using the Ordinary Least Sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…This was confirmed by the finding of Omodan (2020a) that rural areas in South Africa have been neglected and dismembered when it comes to equal distribution of social amenities. In consonance, findings showed that poverty is mostly synonymous with rural dwellers when compared to urban and privileged counterparts (Cheteni & Mah, 2019;Du Toit, 2017). Looking at this, one can deduce that the spirit of Ubuntu as "we are" but "not I am" (Omodan, 2019b, Omodan & Tsotetsi, 2019 is not in operation which has placed the rural leaners at the disadvantaged level during COVID-19.…”
Section: The Challenges Hindering Teachers From Responding To the Psycho-social Vacuum Of Covid-19 On Learners 411 Poverty And Continuousmentioning
confidence: 86%
“…This was confirmed by the finding of Omodan (2020a) that rural areas in South Africa have been neglected and dismembered when it comes to equal distribution of social amenities. In consonance, findings showed that poverty is mostly synonymous with rural dwellers when compared to urban and privileged counterparts (Cheteni & Mah, 2019;Du Toit, 2017). Looking at this, one can deduce that the spirit of Ubuntu as "we are" but "not I am" (Omodan, 2019b, Omodan & Tsotetsi, 2019 is not in operation which has placed the rural leaners at the disadvantaged level during COVID-19.…”
Section: The Challenges Hindering Teachers From Responding To the Psycho-social Vacuum Of Covid-19 On Learners 411 Poverty And Continuousmentioning
confidence: 86%
“…The only barriers for them to participate in different types of learning are related to race, skin color, and religion. Additionally, Cheteni et al (2019) argue that people in the rural and traditional areas were literate regardless of both gender and race. In contrast, those factors are not the case in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has particularly affected poor women. Positioned on the margins of society, such women are dispositioned to experience deprivation and gender‐based violence (Cheteni et al, 2019 ; Segalo, 2015 ; Tibesigwa & Visser, 2016 ).…”
Section: The Key Steps To Successfully Rebuilding Political Engagement After Covid ‐19mentioning
confidence: 99%